Analisis Kinerja Keuangan Untuk Memprediksi Peringkat Obligasi (Studi Pada Perusahaan Properti dan Konstruksi Bangunan Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Indah Permata Sari (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objective of this research is to identify financial factors that affect the rating of corporate bonds. The population of this study is fifteen property and construction companies listed in the Indonesia Stock Exchange in the period of 20122016. Using purposive sampling, nine companies whose Return on Investment is above industrial average were selected as the sample.  This study uses binary logistic regression analysis, while its variables are profitability, leverage, liquidity, and firm growth.The results show  that profitability ratio proxied by Return on Investment (ROI) and liquidity ratio proxied by Cash Ratio (CAR) have a significant effect on bond rating. However, leverage ratio proxied by Debt to Equity Ratio (DER) and firm growth do not have any significant effect on bond rating. In addition, liquidity is the most dominant ratio that affect bond rating. Therefore, bond issuers must observe their profitability and liquidity level to avoid risk of default.    Keywords: bond rating, binary logistic regression, corporate financial performance, profitability, leverage, liquidity, firm growth